Penta-O-Galloyl-β-D-Glucose in Pistacia integerrima Targets AMPK-ULK1 and ERK/STAT3 Signaling Axes to Induce ROS-Independent Autophagic Cell Death in Human Lung Cancer Cells - Acharya Balkrishna; Acharya Balkrishna; Acharya Balkrishna; Vallabh Prakash Mulay; Sudeep Verma; Jyotish Srivastava; Savita Lochab; Anurag Varshney; Anurag Varshney; Anurag Varshney (Frontiers Media S.A., 2022)
Graphical Abstract